The key clock component ZEITLUPE (ZTL) negatively regulates ABA signaling by degradation of CHLH in Arabidopsis - Yu, Yongtao; Portolés, Sergi; Ren, Yi; Sun, Guangyu; Wang, Xiao-Fang; Zhang, Huihui; Guo, Shaogui (Frontiers in Plant Science, 2022)
Ubiquitination-mediated protein degradation plays important roles in ABA signal transduction and delivering responses to chloroplast stress signals in plants, but additional E3 ligases of protein ubiquitination remain to be identified to understand the complex signaling network. Here we reported that ZEITLUPE (ZTL), an F-box protein, negatively regulates abscisic acid (ABA) signaling during ABA-inhibited early seedling growth and ABA-induced stomatal closure in Arabidopsis thaliana. Using molecular biology and biochemistry approaches, we demonstrated that ZTL interacts with and ubiquitinates its substrate, CHLH/ABAR (Mg-chelatase H subunit/putative ABA receptor), to modulate CHLH stability via the 26S proteasome pathway. CHLH acts genetically downstream of ZTL in ABA and drought stress signaling. Interestingly, ABA conversely induces ZTL phosphorylation, and high levels of ABA also induce CHLH proteasomal degradation, implying that phosphorylated ZTL protein may enhance the affinity to CHLH, leading to the increased degradation of CHLH after ABA treatment. Taken together, our results revealed a possible mechanism of reciprocal regulation between ABA signalling and the circadian clock, which is thought to be essential for plant fitness and survival.